Role of the BaeSR two-component system in the regulation of Acinetobacter baumannii adeAB genes and its correlation with tigecycline susceptibility - Lin, Ming-Feng (BioMed Central, 2014)
BACKGROUND: Tigecycline resistance in Acinetobacter baumannii is primarily acquired through overexpression of the AdeABC efflux pump. Besides AdeRS, other two-component regulatory systems (TCSs) involving the regulation of this transporter have not been clarified. RESULTS: In this study, we found that the TCS genes baeR and baeS are co-transcribed and function as stress responders under high osmotic conditions. The baeSR and adeAB genes showed increased transcription in both the laboratory-induced and clinical tigecycline-resistant strains compared with the wild-type strain. The deletion of baeR in the ATCC 17978 strain led to 67–73% and 68% reduction in adeA and adeB expression, respectively, with a resultant 2-fold decrease in the tigecycline minimal inhibition concentration (MIC). In contrast, the overexpression of baeR resulted in a doubled tigecycline MIC, with a more than 2-fold increase in adeA and adeB expression. The influence of baeR knockout on adeAB gene expression can also be observed in the laboratory-induced tigecycline-resistant strain. A time-kill assay showed that the baeR deletion mutant showed an approximate 1-log(10) reduction in colony forming units (CFUs) relative to the wild-type strain when the tigecycline concentration was 0.25 μg/mL throughout the assay period. The wild-type phenotype could be restored by trans-complementation with pWH1266-kan( r )-baeR. Increasing the tigecycline concentration to 0.5 μg/mL produced an even more marked 4.7-log(10) reduction in CFUs of the baeR deletion mutant at 8 h, while only a 2.1-log(10) reduction was observed for the wild-type strain. CONCLUSIONS: Taken together, these data show for the first time that the BaeSR TCS influences the tigecycline susceptibility of A. baumannii through the positive regulation of the resistance-nodulation-division efflux pump genes adeA and adeB.